Physical activity and risk of breast cancer overall and by hormone receptor status: The European prospective investigation into cancer and nutrition. Issue 7 (14th September 2012) - Steindorf, Karen; Ritte, Rebecca; Eomois, Piia‐Piret; Lukanova, Annekatrin; Tjonneland, Anne; Johnsen, Nina Føns; Overvad, Kim; Østergaard, Jane Nautrup; Clavel‐Chapelon, Françoise; Fournier, Agnès; Dossus, Laure; Teucher, Birgit; et al.
Abstract Physical activity is associated with reduced risks of invasive breast cancer. However, whether this holds true for breast cancer subtypes defined by the estrogen receptor (ER) and the progesterone receptor (PR) status is controversial. The study included 257, 805 women from the multinational EPIC‐cohort study with detailed information on occupational, recreational and household physical activity and important cofactors assessed at baseline. During 11.6 years of median follow‐up, 8, 034 incident invasive breast cancer cases were identified. Data on ER, PR and combined ER/PR expression were available for 6, 007 (67.6%), 4, 814 (54.2%) and 4, 798 (53.9%) cases, respectively. Adjusted hazard ratios (HR) were estimated by proportional hazards models. Breast cancer risk was inversely associated with moderate and high levels of total physical activity (HR = 0.92, 95% confidence interval (CI): 0.86–0.99, HR = 0.87, 95%‐CI: 0.79–0.97, respectively; p‐trend = 0.002), compared to the lowest quartile. Among women diagnosed with breast cancer after age 50, the largest risk reduction was found with highest activity (HR = 0.86, 95%‐CI: 0.77–0.97), whereas for cancers diagnosed before age 50 strongest associations were found for moderate total physical activity (HR = 0.78, 95%‐CI: 0.64–0.94). Analyses by hormone receptor status suggested differential associations for total physical activity (p‐heterogeneity = 0.04), with a somewhat stronger inverse relationship for ER+/PR+ breast tumors, primarily driven by PR+ tumors (p‐heterogeneity < 0.01). Household physical activity was inversely associated with ER–/PR– tumors. The results of this largest prospective study on the protective effects of physical activity indicate that moderate and high physical activity are associated with modest decreased breast cancer risk. Heterogeneities by receptor status indicate hormone‐related mechanisms.